Osteopontin/Eta-1 upregulated in Crohn's disease regulates the Th1 immune response. Issue 9 (11th August 2005) - Sato, T; Nakai, T; Tamura, N; Okamoto, S; Matsuoka, K; Sakuraba, A; Fukushima, T; Uede, T; Hibi, T
Abstract : Background and aims: The pathogenesis of Crohn's disease (CD), a chronic inflammatory bowel disease characterised by a Th1 immune response, remains unclear. Osteopontin (OPN) is a phosphoprotein known as an adhesive bone matrix protein. Recent studies have shown that OPN plays an important role in lymphocyte migration, granuloma formation, and interleukin 12 (IL-12) production. The present study investigated expression and the pathophysiological role of OPN in CD. Methods: Plasma OPN concentration was measured by enzyme linked immunosorbent assay. Expression of OPN in human intestinal mucosa was determined using reverse transcription-polymerase chain reaction and western blot, and localisation of OPN was examined by immunohistochemistry. Expression of integrin β3, an OPN receptor, on lamina propria mononuclear cells (LPMC) was assessed by flow cytometry. Functional activation of OPN in LPMC was investigated by measuring the production of cytokines. Results: Plasma OPN concentration was significantly higher in patients with CD compared with normal controls or patients with ulcerative colitis (UC). OPN was upregulated in intestinal mucosa from UC and CD patients. OPN producing cells were epithelial or IgG producing plasma cells, or partial macrophages. OPN was detected in areas surrounding granuloma from mucosa in CD. Integrin β3 expressing macrophages infiltrated inflamed mucosa in UC and CD; in contrast, there was no expression of integrin β3 on intestinal macrophages in normal mucosa. OPN induced production of IL-12 from LPMC in CD but not in normal controls or UC. Conclusions: Increased OPN expression facilitates cytokine production and is closely involved in the Th1 immune response associated with CD.